PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE PADAMATERI TATA SURYA - Ismi Dwi Hastuti; Abdul Ghoni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to create a website-based learning media. The product development adopted the ADDIE model, which guided in designing the training program tools and infrastructure that were effective, dynamic, and supported the training performance itself. The researchers used this model to develop web-based learning media on solar system material.Written interviews (questionnaires) were used to reveal the level of needs at MI. The result of the needs analysis stage obtained that the learning was teacher-centered, the use of media was less attractive, and the internet facilities were not maximal in learning. The criteria of media required for a learning process were developed into web-based science learning media for solar system materials. This product was validated by a material expert, a lecturer at IAIN Salatiga, and was declared feasible after the revision. The sample test was randomly carried out at grade VI students, and the results with an average value of 80.7% were categorized as very feasible. The product effectiveness test was carried out on 30 grade VI students using the paired sample t-test on the questionnaire items. The results obtained that t-count was 8.605with p = 0.00 <0.05. It can be concluded that the pre-test and post-test results had significant changes